m + 2 n = 3 Subtract 2 n to both sides
m + 2 n - 2 n = 3 - 2 n
m = 3 - 2 n
Put this value in equation 2 m + n = 0
2 ( 3 - 2 n ) + n = 0
2 * 3 - 2 * 2 n + n = 0
6 - 4 n + n = 0
6 - 3 n = 0 Add 3 n to both sides
6 - 3 n + 3 n = 0 + 3 n
6 = 3 n Divide both sides by 3
6 / 3 = 3 n / 3
2 = n
n = 2
Now:
m + 2 n = 3
m + 2 * 2 = 3
m + 4 = 3 Subtract 4 to both sides
m + 4 - 4 = 3 - 4
m = - 1
The solutions are:
m = - 1 , n = 2
solve the equation in substitution method 2m+n=0 m+2n=3
14 answers
i dont understand
junior. waec recent paper. math
I don't understand substitution method
I don't understand
Still the same
This is too difficult for me
I don't understand
I now understand thanks
I need more explain
I don't understand the semultaneous linear equation
It's simple
I dont understand the simultaneous equation
I don't understand yet